2016
DOI: 10.1038/srep34936
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical atropine on the choroidal thickness of healthy children

Abstract: The purpose of the current study was to investigate the effect of topical atropine on choroidal thickness using spectral-domain optical coherence tomography. A total of 30 healthy eyes from 30 children were analyzed in this study. A single drop of 1% atropine gel was administered twice daily for a week. Choroidal thickness (CT) was measured using SD-OCT, and changes in CT before and after administration of the eye drops were analyzed at the subfovea and at 1.0-mm intervals (up to 3.0 mm) from the fovea at supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 45 publications
3
61
0
2
Order By: Relevance
“…The current study has also confirmed previous findings that the topical administration of antimuscarinic agents with no optical blur causes an increase in choroidal thickness (Chapter two, Öner et al, 2016;Zhang et al, 2016), and support Nickla and Schrödl (2012) hypothesis that the non-visual choroidal thickening reflects the loss of an excitatory cholinergic input to the choroid.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The current study has also confirmed previous findings that the topical administration of antimuscarinic agents with no optical blur causes an increase in choroidal thickness (Chapter two, Öner et al, 2016;Zhang et al, 2016), and support Nickla and Schrödl (2012) hypothesis that the non-visual choroidal thickening reflects the loss of an excitatory cholinergic input to the choroid.…”
Section: Discussionsupporting
confidence: 79%
“…Choroidal thickness has been shown to be sensitive to a range of antimuscarinics (atropine, homatropine, and cyclopentolate) that significantly increase subfoveal choroidal thickness in humans (Oner et al, 2016;Zhang et al, 2016). In Chapter two we also showed that the muscarinic antagonist (homatropine) can increase choroidal thickness in the human eye.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations